Improving The Quality Of Duroc Boars Semen Through The Application of Sun Dry Carrot Extract In Spermax-Egg Yolk Diluent - Masae, Sinoptis Melkiur; Marawali, Aloysius; Hine, Thomas Mata; Kune, Petrus (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This research aimed to determine the best level of sun-dried carrot extract (SDCE) in the spermax-egg yolk (EY-S) diluent for preserving the sperm of duroc boars. Semen was collected from two 2-year-old healthy duroc boars. The study employed an experimental method with a completely randomized design (CRD), consisting of five treatments and five replicates. The five treatments were T1 = EY-S + SDCE 10%, T2 = EY-S + SDCE 12.5%, T3 = EY-S + SDCE 15%, T4 = EY-S + SDCE 17.5%, T5 = EY-S + SDCE 20%. Semen, which was diluted with the treatment diluent, was stored in a cool box at a temperature of 18-20°C and observed every 12 hours until sperm motility reached 40%. The results indicated that treatment P5 was able to maintain the quality of liquid boar semen better than the other treatments (P<0.05) with sperm motility (46.00%), sperm viability (51.92%), sperm abnormality (4.90%), and sperm survival (66.33 hours). It was concluded that a 20% level of sun-dried carrot extract in spermax-egg yolk diluent can preserve motility for up to 60 hours of storage. This study demonstrates that dried carrot extract can enhance the quality and storage capacity of spermatozoa, making it an effective alternative in storage media. This is beneficial in animal reproduction, particularly in artificial insemination, where sperm motility is crucial for fertilization. Furthermore, this research opens up opportunities to explore other natural substances in sperm diluents, reducing reliance on synthetic chemicals and improving the sustainability of reproductive practices.